Asymptomatic Barrett’s Oesophagus-Complicated Gastroesophageal Reflux Disease at Ineffective Antisecretory Therapy - E. V. Barkalova; S. S. Pirogov; D. N. Andreev; M. A. Ovsepyan; I. V. Maev; A. D. Kaprin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2021)
Aim. A clinical description of gastroesophageal reflux disease (GERD) complicated by Barrett’s oesophagus (BO) at inadequate antisecretory therapy and the assessment of functional tests in control of conservative treatment.Key points. A 63-yo patient with no complaints in a proton pump inhibitor (PPI) therapy was admitted for a follow-up examination for BO-complicated GERD using oesophagogastroduodenoscopy (OGDS) with biopsy, high-resolution oesophageal manometry and 24-h pH-impedance. Endoscopy revealed signs of BO (long segment C1M3), erosive reflux oesophagitis (grade B in Los Angeles classification). Non-contractile oesophagus in manometry. Antisecretory therapy was stated ineffective and subject to correction in 24-h pH-impedance.Conclusion. Asymptomatic BO-complicated GERD patients comprise a special cohort. The main challenge to prevent progression into oesophageal adenocarcinoma is an adequate personalised patient management leveraging the modern diagnostic techniques, control of antisecretory treatment and its correction a situ.